Evaluation of a programming toolkit for interactive public display applications - Cardoso, Jorge C. S. (2014)
Interaction is repeatedly pointed out as a key enabling element towards more engaging and valuable public displays. Still, most digital public displays today do not support any interactive features. We argue that this is mainly due to the lack of efficient and clear abstractions that developers can use to incorporate interactivity into their applications. As a consequence, interaction represents a major overhead for developers, and users are faced with inconsistent interaction models across different displays. This paper describes the results of the evaluation of a widget toolkit for generalized interaction with public displays. Our toolkit was developed for web-based applications and it supports multiple interaction mechanisms, automatically generated graphical interfaces, asynchronous events and concurrent interaction. We have evaluated the toolkit along various dimensions - system performance, API usability, and real-world deployment - and we present and discuss the results in this paper.